Activities of the medical professional self-government in Poland – a perspective of the experiences of its members - Manczak, Iryna; Ciepiela, Katarzyna (Scientific Journal of Bielsko-Biala School of Finance and Law, 2024)
Professional self-government is an example of an independent and autonomous institution that performs several vital tasks provided for in selected legal acts. The legal framework is set by the Act on Medical Chambers, which outlines the fundamental issues determining the scope of the subject matter and the tasks undertaken by the medical representation of the self-government. The district medical chambers exemplify the activities of the medical professional self-government. Membership in the medical professional self-government is an essential condition for practising the profession of medical practitioners. The article aims to identify the perception of the activities of the medical professional self-government by its members. As part of the research methodology developed, a survey was conducted among doctors and dentists. Its participants were medics belonging to district medical chambers. The authors decided to identify the respondents’ opinions on projects undertaken by the chambers and how to communicate them. The results obtained, it can be concluded that the respondents wanted more from the initiatives organised by the medical chambers. During interviews with respondents, the authors identified aspects to consider in formulating future research problems. These problems correlate with issues such as the management of medical chambers’ activities and their organisational culture and leadership.